The Relationship between Reading Interests and English Learning Outcomes of the Fourth Grade Students at SDN Neglasari Serang - Wulandari, Ratih Ayu; Maulana, Apriza Rizky (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2021)
This study aims to determine the positive relationship between reading interest and English learning outcomes of the fourth grade students at SDN Neglasari Serang. This study used a quantitative method with a survey research design. The population of this study amounted to 35 students. The sampling technique used was simple random sampling, with the total number of the sample was 20 students. Research variables consisted of reading interest as the independent variable and the English learning outcomes as the dependent variable. Data collection techniques included interviews, questionnaires and documentation. Data analysis was employed by using statistical analysis, normality test, homogeneity test, regression linearity test and significance, hypotheses testing and coefficient of determination. The results of the study showed that there was a positive and significant relationship between reading interest and English learning outcomes, the value of r count = 0.478 and it was categorized as sufficient and contributed for 47.8%. This study concluded that there was a significant positive relationship between reading interest and English learning outcomes at SDN Neglasari Serang.